Journal Economics, business & accountancy : THE ANALYSIS OF INDONESIA ECONOMIC GROWTH: A STUDY IN SIX BIG ISLANDS IN INDONESIA - Christianto Leasiwal, Teddy (PPPM Perbanas, 2013)
This study attempts to investigate and analyze the factors determining and influencing the Indonesiaseconomic growth, and to see economic growth in the six bog islands in Indonesia, usingextension of the Solow-Swan model and endogenous growth models, by also adding the factors ofeducation (EDU), the potential sectors utilization (PSU) as well as several other factors that ForeignDirect Investment (FDI), Political Stability and Security (STAB)